The classification of funeral services - Похиленко, Ірина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Statutory regulation of funeral services is presented in the Tax Code of Ukraine, the Law of Ukraine ‘About Burial and Funeral Business’, national classifier of Ukraine DK 009: 2010’ “Classification of Economic Activities", ratified by the State Committee of Ukraine for Technical Regulations and Consumer Policy, the List of Derggitlokomungosp (Public Housing Utilities) of Ukraine "The Necessary Minimum List of Requirements for the Procedure of Organization of Funeral and Ritual Services for the Population. Their analysis and scientific approaches can determine the classification of funeral services based on the following criteria: According to the number of subjects engaged in the organization of funeral they can be classified as follows: 1) central executive authorities ensuring public policy in the housing and utilities sector; 2) local authorities; 3) local governments and their executive bodies; 4) funeral services. In terms of payment they can be divided into paid funeral services and funeral services free of charge. According to the validity of statute which provides the procedure of funeral services: 1) funeral services provision of which is prescribed by law; 2) funeral services provision of which is prescribed by statutory instruments. According to the material content: 1) tangible funeral services, most of which are material in nature (making coffins); 2) intangible services that are characterized by intellectual activities (music burial rite). Depending on the social status of the deceased: 1) the burial of deceased persons who have special merits before the Motherland, combatants, war invalids; 2) burial of the dead soldiers, police officers and other ranks, the State Penitentiary Service of Ukraine, State Service for Special Communications and Information Protection of Ukraine and the officers and other ranks of the tax police; 3) burial of deceased lonesome citizens; 4) burial of the dead who lived in various types of special institutions; 5) burial of deceased who served sentences in prisons or detention centers; 6) burial of infected body.